Efeitos do cádmio no arroz (Oryza sativa L.) e no feijoeiro (Phaseolus vulgaris L.) cultivados em soluções nutritivas - Gaona Jurado, Santiago (1989)
Several experiments were carried out in order to study the effects of Cd supply on growth, symptomatology, and mineral composition of rice ( Oryza sativa L., cv IAC 4440) and bean ( Phaseolus vulgaris L., cv Carioca 80) plants. Cd was supplied at the levels of 0.00, 0.05, 0.50 and 5.00 ppm for rice and 0.0000, 0.0025, 0.0050, 0.0500, and 0.5000 for the bean plants, based on preliminar experiments. Rice plants were collected for growth and mineral analysis at maximum tillering and panicle formation, whereas bean plants were harvested both at flowering and pod formation. Chief conclusions are as follows: 1) Increasing levels of Cd in the nutrient solution affected the growth both of tops and roots. 2) The most conspicuous symptom of toxicity was the presence of reddish brown specks on leaves, petioles and stems of the bean plant, and on rice leaves. 3) Cd concentrations lower or equal to 0.05 ppm had a beneficiaI effect on the growth of rice, as well as on the content of all nutrients which were analysed (N, P, K, Ca, Mg, Cu, Fe, Mn, Zn). Higher concentrations, however, had the opposite effect on mineral composition, exception made for the elements Cu, Fe, and Mn. 4) In a genera1 way, Cd had a depressive effect on the growth of bean plants, as well as in the accumulation of N, K, Ca, Mg and Zn. 5) The largest proportion of Cd taken up by both species was concentrated in the root system. 6) Relatively speaking, a more pronounced inhibition on the long distance transport of Cd was observed in beans. 7) Bean plants were much more sensitive to Cd toxicity than rice.